EMERGED LANGUAGE TEACHING METHODOLOGIES IN POLYTECHNIC: CORPUS LINGUISTICS AND DIALOGIC PEDAGOGY IN POLYTECHNIC: CORPUS LINGUISTICS AND DIALOGIC PEDAGOGY - Ilham Jaya; Hasyimi Abdullah; Amru Muhammad; Wahdaniah Wahyudi; Emilda Emilda (Universitas Syiah Kuala, 2020)
This study discusses the emerged language teaching methodologies practiced in Engineering Fields. There are many methods applied in teaching language. However, the needs of technical fields in English learning, especially for workforce, academic and social demand, seemed to have appropriate treatment. Career choice has given a great impact influencing the study of English language. In addition, there are specific needs in the engineering workplace that are inevitably used by engineers to correspond with their colleagues or customers. This situation leads to some thought in English for specific purpose practices. Recently, there are two teaching methodologies adjusted for the needs of technical school students that are being studied. First, Corpus linguistics: the lexical approach has been mostly practiced before. Innovated by data-driven corpus, this methodology arises as to the new common method applied in the engineering area. Second, Dialogic Pedagogy: the thought of dialogism is grounded by the sociocultural theory that considers learning as a social act. Social engagement is believed in improving one’s ability to be a decider and problem solver. Through dialogic pedagogies, students learn to eliminate some problems related to language barriers, such as the anxiety to speak English and apprehensiveness in making mistakes.